ENHANCING FUNCTIONAL RECOVERY AFTER HIP ARTHROPLASTY WITH BALNEOTHERAPY: IMPROVING HIP ARTHROPLASTY RECOVERY WITH BALNEOTHERAPY - Klimó, Attila; Jeremić, Rada; Brkić, Predrag; Bogetić, Mina; Babić, Marija (Medical Research, 2024)
Introduction: Balneotherapy is a therapeutic approach that utilizes natural elements as a means of treatment. Hip arthroplasty is a surgical procedure that helps address hip joint dysfunction, and it has proven to be effective. This study aims to investigate whether the use of thermal mineral water can enhance the recovery of functional capabilities and improve the quality of life of patients who have undergone hip arthroplasty.Material and Methods: The study involved patients (n=100) who had undergone hip arthroplasty and participated in hydrokinesis exercises in pools containing thermal mineral water, in addition to a conventional therapeutic rehabilitation program on dry land. The evaluation included assessments of the range of motion of the hip joint and the strength of key hip-joint-moving muscles. Respondents also rated the success of the protocol based on improvements in quality of life parameters.Results: The results of the study showed that the use of balneological agents from the specific thermal mineral water source "Banja Kanjiža" significantly expedited the recovery of functional abilities and augmented the quality of life in patients who had undergone hip arthroplasty surgery. Conclusion: To further verify the effectiveness of balneotherapy, coordinated multicenter clinical trials and fundamental research are essential. Persistent efforts to extend the benefits of natural healing agents, the expertise of qualified health professionals, and the infrastructure of developed spa centres for residents and the global populace are also important.Keywords: balneotherapy, hip arthroplasty, rehabilitation
Keywords: balneotherapy, hip arthroplasty, rehabilitation